Teacher and Students’ Oral Interaction in EFL Classroom: A Structural Discourse Analysis - Vivi Safitri; Alek Alek; Didin Nuruddin Hidayat; Nida Husna (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
This study aims to examine and discuss the interaction structure of teacher and student oral discourse in class MI As-Syafi'iyah 06 Kab. Bogor. This study uses a qualitative approach using a descriptive methodology. The participants in this study were 30 students and one teacher in class 5 MI As-Syafi'iyah 06 Kab. Bogor. The instrument used in this research is documentation by recording. The results of the study show that the interaction between teachers and students in class is based on the theory put forward by Ramirez (1988). The structure of the oral discourse of teacher and student interaction shows that interaction in the classroom has three layers of exchange, action, movement, and exchange. The results of this study are more focused on one of the discourse structures proposed by Ramirez, namely action. Existing agreements are small interactions involving two or more participants. The agreement is formed in a series of turns consisting of triggering from the teacher, responses from students, and feedback from the teacher. The structure of the Interaction action shows the exchange which is formulated as opening, responding, and following up.